Factors Related to Functional Independence in Daily Activities of Older People with Osteoarthritis in Mashhad, Iran in 2016 - Ahmadpour, Mahboubeh; Darvishpoor Kakhki, Ali; Zandi, Mitra; Nourbakhsh, Ramin (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Osteoarthritis is one of the leading causes of disability and reduction of functional independence in older people. The present study was conducted to investigate the factors related to functional independence in daily activities of older people with osteoarthritis in Mashhad, Iran. Methods: In this descriptive-correlational study, 300 older people with osteoarthritis who had referred to rheumatology clinics of Mashhad University of Medical Sciences Hospitals in Mashhad in 2016 were selected and entered in the study by available sampling method. Data collection tools in this study included demographic information questionnaire and scale of activities of daily living, the validity and reliability of which were measured. SPSS-21 software was used for data analysis. Results: The age average of the study subjects was 70.75 (± 7.27). The older people with higher education levels, male gender, married and who lived with a spouse or spouse and children, lower in age, economically independent (higher income and working), lower body mass index, the ones with less duration of osteoarthritis, ones who did not need to use assistive devices, did not suffer from the lack of joint mobility, and did not have hip osteoarthritis, had more independence in activities of daily living (P value < 0.05). Conclusions: According to the obtained results and related factors from this study, it is necessary that more accurate planning be considered to prevent, control and manage factors leading to the dependence of older people.